Stakeholder Analysis in the Management of Marine Conservation Area in Indragiri Hilir District - Deviasari, Deviasari; Rosnita, Rosnita; Warningsih, Trisla; Yunita, Aprilla (Jurnal Perikanan dan Kelautan, 2023)
Various human activities around the marine protected area in Indragiri Hilir Regency put considerable pressure on coastal and marine ecosystems. The Marine Protected Area of ​​Solop Beach Pulau kecil Park in Indragiri Hilir Regency has been designated as a marine protected area to protect water areas, with a zoning system to realize sustainable management of fish resources and the environment. The research was carried out in October 2022 in the marine protected area in Indragiri Hilir Regency. This study aims to analyze the role of stakeholders involved in the management of marine protected areas in Indragiri Hilir Regency, which was carried out through in-depth interviews with informants, namely selected stakeholders. The results showed that the role of stakeholders in the management of marine protected areas in Indragiri Hilir Regency was grouped into: input (Provincial Environment and Forestry Service, Provincial Maritime Affairs and Fisheries Service and Ministry of Maritime Affairs and Fisheries), stake (Village Head), output (Managers, group’s community, fishermen, and NGOs) and unused (Academics).